The Role of Carotid Sinus Nerve Input in the Hypoxic-Hypercapnic Ventilatory Response in Juvenile Rats - Getsy, Paulina M.; Coffee, Gregory A.; Lewis, Stephen J. (Frontiers in Physiology, 2020)
In juvenile rats, the carotid body (CB) is the primary sensor of oxygen (O2) and a secondary sensor of carbon dioxide (CO2) in the blood. The CB communicates to the respiratory pattern generator via the carotid sinus nerve, which terminates within the commissural nucleus tractus solitarius (cNTS). While this is not the only peripheral chemosensory pathway in juvenile rodents, we hypothesize that it has a unique role in determining the interaction between O2 and CO2, and consequently, the response to hypoxic-hypercapnic gas challenges. The objectives of this study were to determine (1) the ventilatory responses to a poikilocapnic hypoxic (HX) gas challenge, a hypercapnic (HC) gas challenge or a hypoxic-hypercapnic (HH) gas challenge in juvenile rats, and (2) the roles of CSN chemoafferents in the interactions between HX and HC signaling in these rats. Studies were performed on conscious, freely-moving juvenile (P25) male Sprague Dawley rats that underwent sham-surgery (SHAM) or bilateral transection of the carotid sinus nerves (CSNX) 4 days previously. Rats were placed in whole-body plethysmographs to record ventilatory parameters (frequency of breathing, tidal volume and minute ventilation). After acclimatization, they were exposed to HX (10% O2, 90% N2), HC (5% CO2, 21% O2, 74% N2) or HH (5% CO2, 10% O2, 85% N2) gas challenges for 5 minutes, followed by 15 minutes of room-air. The major findings were: (1) the HX, HC and HH challenges elicited robust ventilatory responses in SHAM rats; (2) ventilatory responses elicited by HX alone and HC alone were generally additive in SHAM rats, (3) the ventilatory responses to HX, HC and HH were markedly attenuated in CSNX rats compared to SHAM rats, and (4) ventilatory responses elicited by HX alone and HC alone were not additive in CSNX rats. Although the rats responded to HX after CSNX, CB chemoafferent input was necessary for the combined response to HH challenge. Thus, secondary peripheral chemoreceptors do not compensate for the loss of chemoreceptor input from the CB in juvenile rats.